Intercellular mitochondrial transfer through nanotubules is promoted by cyclic amp (cAMP) in rat astrocytes and human glioblastoma cells - Helfenberger, Katia Estefanía (2020)
Nanotubules (Tunneling nanotubules, TnTs) are cell membrane projectionsmade of F-actin fibers of nanometric diameter (up to 1 μm),which enable cytoplasmatic connections between cells. It has beenshown that mitochondria, other organelles, and cellular componentsare transferred by TnTs in several normal and tumor cell lines. TnTsestablishment has been extensively described in nervous systemcells, as neurons and astrocytes. Published evidence indicates theexistence of mitochondrial transfer through TnTs between differentcell types, such as normal and tumoral cells. Mitochondrial passagefrom normal to tumor cells restores oxidative metabolism, decreasingtumorigenic potential. A similar effect has been observed withcAMP, a very well-known astrocytes stellation promoter, which mediatesmitochondrial biogenesis and tumor growth inhibition. Mitochondrialtransfer within TnTs in nervous system cells have not beendemonstrated so far. Then, our goal was to analyze mitochondrialtrafficking through TnTs in normal and tumoral astrocytes and apossible effect of cAMP. We used normal rat astrocytes and humanglioblastoma U87 cells. Mitochondria and actin were probed with amito-targeted green fluorescent protein and phalloidin, respectively.Astrocytes and U87 were incubated with or without 8Br-cAMP(cAMP analogue). We analyzed images by confocal microscopy andmeasured the width of actin connections between cells. We analyzedeach culture separately; astrocytes and U87 establish thick projectionscontaining mitochondria but treatment with cAMP promotes anincrease of TnTs-like connections with mitochondria inside (controlvs cAMP: astrocytes: 2.07±0.71 vs 0.85±0.21 μm, ***p<0.05; U87:2.69±1.40 vs.0.84±0.22 μm, *p<0.05, ± SD, ANOVA, Tukey test).Thus, cAMP promotes TnTs-like structures and mitochondrial passagethrough them in normal astrocytes and glioblastoma cells, suggestinga role for intercellular mitochondrial transfer through TnTs instellation process.